2007
DOI: 10.1111/j.1445-2197.2007.04288.x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Hepatectomy, a Systematic Review

Abstract: This systematic review was undertaken to assess the published evidence for the safety, feasibility and reproducibility of laparoscopic liver resection. A computerized search of the Medline and Embase databases identified 28 non-duplicated studies including 703 patients in whom laparoscopic hepatectomy was attempted. Pooled data were examined for information on the patients, lesions, complications and outcome. The most common procedures were wedge resection (35.1%), segmentectomy (21.7%) and left lateral segmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 42 publications
1
38
0
1
Order By: Relevance
“…Since then, with the introduction of various new and improved laparoscopic devices, laparoscopic liver resection has been increasingly adopted worldwide and numerous series have been published in the literature. [3][4][5] Laparoscopic liver resection has been shown to be superior to open liver resection in terms of postoperative outcomes such as decreased pain and shorter hospital stay. [3][4][5] It has also been shown to be safe with blood loss, blood transfusion rates, postoperative morbidity rates, and postoperative mortality rates that are similar to, if not lower than, those with open surgery.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since then, with the introduction of various new and improved laparoscopic devices, laparoscopic liver resection has been increasingly adopted worldwide and numerous series have been published in the literature. [3][4][5] Laparoscopic liver resection has been shown to be superior to open liver resection in terms of postoperative outcomes such as decreased pain and shorter hospital stay. [3][4][5] It has also been shown to be safe with blood loss, blood transfusion rates, postoperative morbidity rates, and postoperative mortality rates that are similar to, if not lower than, those with open surgery.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Laparoscopic liver resection has been shown to be superior to open liver resection in terms of postoperative outcomes such as decreased pain and shorter hospital stay. [3][4][5] It has also been shown to be safe with blood loss, blood transfusion rates, postoperative morbidity rates, and postoperative mortality rates that are similar to, if not lower than, those with open surgery. [3][4][5][6] Numerous investigators have also confirmed its effectiveness for treating malignant lesions such as hepatocellular carcinoma (HCC), reporting similar tumor-free margins and survival rates compared with open resection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Since then, laparoscopic LR has been increasingly adopted worldwide, with numerous case series from various institutions in Europe, Asia, and the United States reported in the literature. [2][3][4][5] However, because of the technical complexity of the totally laparoscopic approach, various other minimally invasive approaches have been described for LR, including the hand-assisted laparoscopic (HALS) and laparoscopicassisted (hybrid) approaches. 2,6 There has been no clear demonstrable advantage or definitive selection criteria for the various approaches, although in general the handassisted or hybrid approaches have been used for more "technically challenging" operations such as major hepatectomy, resection of larger tumors, tumors close to major vasculature, and tumors arising from difficult locations such as the right posterior or superior segments.…”
Section: Introductionmentioning
confidence: 99%
“…durchgeführt werden. Laparoskopische Resektionen werden in erfahrenen Zentren zunehmend durchgeführt, stellen aber noch kein Standardvorgehen dar [154,155].…”
Section: Chirurgische Strategieunclassified